Posterior insular cortex – a site of vestibular–somatosensory interaction?. Issue 5 (23rd July 2013) - Baier, Bernhard; Eulenburg, Peter zu; Best, Christoph; Geber, Christian; Müller‐Forell, Wibke; Birklein, Frank; Dieterich, Marianne
Abstract Background In previous imaging studies the insular cortex (IC) has been identified as an essential part of the processing of a wide spectrum of perception and sensorimotor integration. Yet, there are no systematic lesion studies in a sufficient number of patients examining whether processing of vestibular and the interaction of somatosensory and vestibular signals take place in the IC. Methods We investigated acute stroke patients with lesions affecting the IC in order to fill this gap. In detail, we explored signs of a vestibular tone imbalance such as the deviation of the subjective visual vertical (SVV). We applied voxel‐lesion behaviour mapping analysis in 27 patients with acute unilateral stroke. Results Our data demonstrate that patients with lesions of the posterior IC have an abnormal tilt of SVV. Furthermore, re‐analysing data of 20 patients from a previous study, we found a positive correlation between thermal perception contralateral to the stroke and the severity of the SVV tilt. Conclusions We conclude that the IC is a sensory brain region where different modalities might interact.